INVENTARISASI JENIS-JENIS TUMBUHAN FAMILI EUPHORBIACEAE DI KECAMATAN TOPOS KABUPATEN LEBONG PROVINSI BENGKULU - Nopa Nopi Yanti; Linna Fitriani (Jurnal Biosilampari : Jurnal Biologi, 2019)
This study aims to determine the types of plants of the Euphorbiaceae family in Topos District, Lebong Regency, Bengkulu. The research was conducted in May-June 2018 in 7 villages in Topos District, Lebong Regency, Talang Baru 1 Village, Talang Baru 2 Village, Talang Donok 1 Village, Talang Donok 2 Village, Anjay Siang Village, Suka Negri Village, and Villages Bandar Agung. The study was conducted by survey and interview the specimens were taken and analyzed descriptively. From the results of the study founded 20 plant spesies Euphorbiaceae family with 11 genera, namely: Acalypha 1 spesies (Acalypha indica), Aleurites 1 spesies (Aleurites maluccana), Codiaeum 5 spesies (Codiaeum Sp, Codiaeum 'Finger', Codiaeum 'Cronstandt', Codiaeum variegatum 'Norma', Codiaeum variegatum 'Exsotica red'), Euphorbia 4 spesies (Euphorbia hirta, Euphorbia pulcherrima, Euphorbia milli, Euphorbia milli 'Golden eagle'), Excoecaria 1 spesies (Excoecaria chinchinensis), Hevea 1 spesies (Hevea brasilensis), Jartopha 2 spesies (Jatropha curcas, Jatropha gossypiifolia), Manihot 1 spesies (Manihot esculenta), Pedilanthus 1 spesies (Pedilanthus tithymaloides), Phyllanthus 2 spesies (Phyllanthus urinaria, Phyllanthus acidus), Sauropus 1 spesies (Sauropus androguns).